The Effectiveness of Media Games Books and Big Books on the Learning Outcomes of Indonesia Language for Elementary School Students - Miftahur Rohmah; Muhamad Taufik Hidayat (Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
Currently, there are still many students who have difficulty in understanding a reading, it is necessary to have tools, namely learning media. Learning media is one of the inseparable learning tools that must be able to be selected and used by teachers in the process of learning activities. The purpose of this study is to analyse the effectiveness between Games Book media and Big Book media in improving the learning outcomes of third grade students in Indonesian lessons. This type of research is comparative to a pseudo-experimental approach. The subjects in this study were third grade students of elementary school consist of 36 students. The data collection method uses tests to assess and measure student learning outcomes. The test for data analysis related to validity of the questions uses Product Moment Correlation, while the reliability test uses Cronbach's Alpha method. Normality test using Liliefors method, homogeneity test using F test, while hypothesis test using Independent Sample T-Test. In this study, it is shown that media games books and big books can improve the learning outcomes of third grade students of elementary school in Indonesian lessons. Meanwhile, media games books are more effective in improving student learning outcomes than big book media.